POSTGRADUATE STUDENTS` PERCEPTIONS ON THE INTEGRATION OF TECHNOLOGY AND ISLAMIC VALUES IN ENGLISH LANGUAGE LEARNING AT ISLAMIC HIGHER EDUCATION - Sharmila Azmita; Darliyati Lubis (Universitas Negeri Islam Sumatera Utara, 2025)
This study addresses postgraduate students' perspectives regarding the integration of technology and Islamic values in English Language Learning (ELL) within Islamic higher education in Indonesia. The primary aim is to comprehend how students perceive the interplay between digital innovation and moral education within their academic experience. A qualitative descriptive methodology was employed to gather data using questionnaires, which was subsequently augmented by semi-structured interviews with ten postgraduate students from Islamic universities. The qualitative design facilitated a comprehensive knowledge of students' experiences, attitudes, and ethical considerations. The results indicate that students exhibit robust digital proficiency, favorable attitudes towards technology utilization, and elevated ethical consciousness informed by Islamic principles. Nonetheless, the incorporation of Islamic principles into English education is patchy and differs among courses and teachers. Participants underscored the significance of integrating sincerity, discipline, and accountability into technology-driven learning activities. The research indicates that technology, when integrated with faith-based principles, can improve both language skills and ethical development. Thus, Islamic higher education institutions ought to formulate organized curricula and faculty development initiatives that foster ethical and value-oriented digital learning environments.